# What is 2/3 + 2/6? getcalc.com's two fractions addition calculator is an online basic math function tool to find what's the equivalent fraction for sum of two fractional numbers with different, unequal or unlike denominators 2/3 and 2/6.

2/3 + 2/6 = 6/6 as simplified as 1/1 in fraction form

2/3 + 2/6 = 1 in decimal form
This calculator, formula, step by step calculation and associated information for adding 2/3 & 2/6 may help students, teachers, parents or professionals to learn, teach, practice or verify such two fractions addition calculations efficiently.

## How to Find Equivalent Fraction for 2/3+2/6?

The below workout with step by step calculation shows how to find the equivalent fraction between 2/3 and 2/6 by adding two fractions with different, unequal or unlike denominators. The sum in fraction form for 2/3 plus 2/6 can be obtained by using anyone of the two methods below.
1. LCM method
2. Cross multiplication method.

Problem & Workout - LCM Method
What is 2/3 plus 2/6 as a fraction by addition using LCM method?

step 1 Address formula, input parameters & values.
Input parameters & values:
2/3 & 2/6
2/3+2/6 = ?

step 2 For unequal denominators, find the LCM (least common multiple) for both denominators
The LCM for 3 and 6 is 6.

step 3 To have the common denominator, multiply the LCM with both numerator & denominator
=(2 x 6)/(3 x 6)+(2 x 6)/(6 x 6)
=4/6+2/6
=(4 + 2)/6

step 4 Add both numerator and rewrite it in a single form.
= 6/6
=1/1
2/3+2/6=1/1

By using LCM method, 1/1 is the equivalent fraction by adding 2/3 and 2/6.

Problem & Workout - Cross Multiplication Method
step 1 Address formula, input parameters & values.
Input parameters & values:
2/3 & 2/6
2/3 + 2/6 = ?

step 2 Cross multiply both numerator & denominator, multiply both denominators and rewrite as below
= (2 x 6) + (2 x 3)/(3 x 6)

step 3 Simplify & rewrite the fraction
= (12 + 6)/18
= 18/18
= 1/1
2/3+2/6 = 1/1
By using cross multiplication method, 1/1 is the addition between two fractions 2/3 and 2/6. 